Dental plaque pH recovery effect of arginine bicarbonate rinse in vivo - Wang, Xiao Ling; Cheng, Chuo Yue; Peng, Dong; Wang, Bing; Gan, Ye Hua (Chinese journal of dental research, 2012)
To investigate the neutralising effects of subsequent arginine bicarbonate rinse on sucrose-induced decrease in plaque pH with interdental plaque pH telemetry. Six participants wearing partial lower prostheses incorporating a miniature glass pH electrode were included. After 5 or 6 days of plaque accumulation on the tip of the electrode, the subjects rinsed with a 15 ml 10% sucrose solution, followed no subsequent rinsing or rinsing with 15 ml of water, or 85 mmol/L NaHCO3, or 0.5%, 1% or 2% arginine bicarbonate for 2 min. The plaque pH was continuously recorded for 120 min. Without a subsequent rinse, the plaque pH decreased at 10 min to 4.38 and stayed below the critical 5.7 for 83 min after sucrose rinse. Subsequent water rinse showed little effects on the sucrose-induced decrease in plaque pH and NaHCO3 induced only an instantaneous pH rise, whereas subsequent arginine bicarbonate rinses all immediately and effectively neutralised the sucrose-induced decrease in plaque pH. These results strongly suggested that regular use of an arginine bicarbonate rinse after carbohydrate consumption could help prevent caries.